2021
DOI: 10.1002/isd2.12171
|View full text |Cite
|
Sign up to set email alerts
|

Digital inclusion of the Orang Asli of Peninsular Malaysia: Remote virtual mechanism for usability of telecentres amongst indigenous peoples

Abstract: Over the last decades, researchers and development practitioners have been experimenting with models, frameworks and devises to meet the needs of diverse users of information communication technologies. Turning to an ICT‐based community development known as the Telecentre Programme amongst Orang Asli, an indigenous people groups in Peninsular Malaysia, this paper describes why a remote virtual management devise was invented to encounter challenges related to rugged terrain constraints, which would have directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…This strength has dramatically improved the overall health and wellbeing of the community. The results of this study are consistent with previous research by Rashid and Hassan (2012) and Bala and Tan (2021), which have shown that the telecenter model can effectively empower rural communities such as the Orang Asli by providing them with access to modern communication facilities. This strength, in turn, has the potential to contribute to the overall well-being and development of the community.…”
Section: Fig 1: Summary Of Swot Analysis: Identification Of Strengths...supporting
confidence: 92%
See 1 more Smart Citation
“…This strength has dramatically improved the overall health and wellbeing of the community. The results of this study are consistent with previous research by Rashid and Hassan (2012) and Bala and Tan (2021), which have shown that the telecenter model can effectively empower rural communities such as the Orang Asli by providing them with access to modern communication facilities. This strength, in turn, has the potential to contribute to the overall well-being and development of the community.…”
Section: Fig 1: Summary Of Swot Analysis: Identification Of Strengths...supporting
confidence: 92%
“…Rashid and Hassan (2012), for instance, demonstrated the potential benefits of ICT for rural communities in Malaysia, such as balancing urban and rural development by bridging the digital divide, improving access to information, increasing economic opportunities, saving time and money, empowering the community, and enhancing the quality of rural community life. Similarly, Bala and Tan (2021) have highlighted that the development of ICT in rural areas has increased the ability of rural communities to access information through digital collaboration, created low-cost platforms for knowledge sharing, promoted local capacity building, and increased the confidence of local communities, as well as reducing dependence on technology from external sources. Additionally, telecenter development in rural areas has provided adequate access to government applications and current information and issues (Gomez et al, 2012), generate employment and business opportunities (Bailey and Ngwenyama, 2013), serve as an entertainment platform (Sey et al, 2013), and function as a management tool (Sey et al, 2013;Tahir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Temiar tribe, for instance, assign a prominent place to dreams as repositories of insight and knowledge (Masron et al, 2013). For all groups, land is more than just a commodity; it is a touchstone of culture and identity, there being no acknowledged gap between human life and nature (Bala & Tan, 2020; Dong et al, 2022). In these respects, even the terms individual and society as normally used cannot be taken for granted: their meanings for the Orang Asli are not what they would be for a person with a different background.…”
Section: The Orang Asli As a Marginalised Groupmentioning
confidence: 99%
“…The out-of-the-way locations of these indigenous communities create immense distance both in time and space and therefore exemplify the disconnected portion of the digital divide in Malaysia. They are often are without network access, lack of adjacent infrastructure (e.g., grid electricity), lack of digital and language literacy, low income and affordability, lack of relevant content and services as well as lack of cultural and social relevance and therefore acceptance [19]. See Table 1 for a complete list of the indigenous communities involved.…”
Section: Background Contextmentioning
confidence: 99%